Birding and Avitourism: Potential Analysis of Birds in the Buffer Villages Around Conservation Area - Dian Iswandaru; Hariyono; Fathur Rohman (Jurnal Sylva Lestari, 2023)
The development of avitourism in villages around the conservation area still needs optimal support to increase welfare and reduce illegal practices like bird hunting. Birds are wild animals that play an essential role in the ecosystem. One of the efforts that have been developed in the buffer village to improve the welfare community and the conservation of birds is avitourism. This study aimed to analyze birds that have the potential as objects and attractions in avitourism. The bird species recorded were 82 species from 39 families. The results of key informants’ perception analysis revealed that 55 bird species (67.07%) have the potential as objects and attractions of avitourism, showing the nocturnal birds, top 50 birds of Way Kambas National Park, and parrot species as the top classification (> 75%). The colorful, raptor, and protected criteria are second with the favorite classification (51-75%). Endemic and migrant criteria are in the third position with the impressive classification (25-50%), and the songbird criteria are the lowest with the interesting classification (< 25%). The existence of birds that have the potential as objects and attraction of avitourism in the villages around Way Kambas National Park indicates that areas can be used in locations for avitourism, including bird photography, to improve welfare. Keywords: Avitourism, birds, buffer villages, Way Kambas National Park